Impact of TikTok Store Closing: Communication Analysis and User Response - Muhamaad Fikri Akbar; Immawati Asniar; Yuli Evadianti (Jurnal Komunikasi, 2024)
In this study, we investigate the impact of the TikTok Shop closure, focusing on communication analysis and user responses. Engaging active participation from respondents, we gained deep insights into how this closure decision affects users in the context of online communication. The research methods involved surveys and qualitative analysis of user responses. The study's results show a variety of user reactions, including disappointment, frustration, and adaptation to the change. Communication factors, such as the clarity of information and user engagement, were identified as key elements influencing their perceptions of this decision. In-depth analysis of the data highlights the crucial role of communication in managing negative impacts and the potential to rebuild user trust through transparency and better interaction. Additionally, this research explores broader implications related to crisis management and communication strategies of digital platforms when facing sudden changes. The findings indicate that effective and transparent communication can mitigate negative reactions and help users adapt to unexpected changes. Thus, this study not only provides a deep understanding of user responses to the TikTok Shop closure but also emphasizes the importance of effective communication in overcoming challenges in a dynamic digital environment. These findings are expected to offer valuable guidance for practitioners, researchers, and decision-makers involved in managing similar digital platforms. The conclusion of this study is that a good communication strategy can minimize negative impacts and enhance user trust, ultimately contributing to the long-term success of digital platforms.